Nitrogênio no feijoeiro em sistema de plantio direto sobre gramíneas - Gomes, Francisco Guilhien; de Sa, Marco Eustaquio [UNESP]; Valerio Filho, Walter Veriano [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
An adequate supply of nitrogen is essential for high yield of common bean seeds; however, the responses to this nutrient in no-tillage systems can vary in function of the species and the amount of straw present. The aim of this research was to evaluate response of the common bean to N in no-tillage systems over maize, millet and Brachiaria brizantha crop residues. Three experiments were conducted, one for each gramineous species. The experimental design was a randomized block in a 5x2x2 factorial scheme, with five N doses (0, 30, 60, 90, 120 kg ha(-1)), in two distinct stadia during the vegetative development (3(rd) and 6(th) trifoliate leaf) and two common bean cultivars (IPR Juriti and Perola), with four replications. The IPR Juriti produced a greater number of pods per plant and showed lower mass per 100 seeds than Perola. It did not show variation in bean yield when the sidedressing N application was carried out in the 3(rd) or 6(th) trifoliate leaf stadia. Based on the obtained results, one concludes that the seed productivity of common beans increases linearly with N doses in a no-tillage system over maize residues.
Nitrogen in common bean in no-tillage system over gramineae
Keywords: Phaseolus vulgaris L.; mulching; nitrogen fertilizer; phenology; seed yield